Smart urban toilet design to meet physiological needs for homeless people in Costa Rica - Rojas-Jiménez, Andrea M. (2021)
The city of San José has the highest rate of homeless people in Costa Rica. This sector of the population is usually marginalized by society and has deficiencies when it comes to meeting their basic needs. During the project, these deficiencies were studied in order to define which ones could be solved through the design of a smart product, with the idea of improving their quality of life.A digital ethnography was carried out with the purpose of obtaining relevant information on the subject. The most important needs were investigated, based on that, the decision to develop a sanitary waste management product was made, which involves biological, security and belonging needs.  The development of the product required a design concept that included the definition and validation of requirements according to the need specified, a market study and the analysis of existing analog products.  Once those aspects were defined, the practical and smart functions were detailed along with the needed components, perception, ergonomics, shape, interaction, assembly, installation, materials and their respective manufacturing processes. This resulted in SU, a smart urban toilet developed by using high-quality 3D modeling and rendering. This design limits the contact product-user and raises a periodical automatic disinfection by using sensors and light. Besides, it’s a modular stainless steel product, which makes it fabrication and multiple assembly easier.This product represents a social and individual contribution of design, it’s implementation indirectly reduces the pollution for sanitary waste in public areas and benefits homeless people directly.